1966
DOI: 10.1161/01.res.19.4.689
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Ventricular Defibrillation with Triangular and Trapezoidal Waveforms

Abstract: From 7,200 fibrillation-defibrillation episodes in anesthetized dogs, the effectiveness of 6 classes of unidirectional shocks in reversing ventricular fibrillation of 30-sec duration was determined. The shocks lasted for 1 to 256 msec. Three waveforms (ascending ramp triangular, descending ramp triangular, and trapezoidal) were studied at peak currents of 10 amp and 20 amp. Families of curves of per cent success vs. energy were derived from the data for the 6 classes of waveforms studied and from corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0
1

Year Published

1973
1973
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…As the field of clinical defibrillation matured, numerous studies were devoted to find the optimal shock waveform that would accomplish defibrillation with minimal delivered energy. It was shown that morphologically distinct waveforms have different defibrillation efficacies in both experimental studies (18,19,26,32,42) and theoretical studies using lumped models (16,43). However, the experimental studies that elucidate mechanisms for differences in defibrillation efficacies of the various waveforms are lacking.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As the field of clinical defibrillation matured, numerous studies were devoted to find the optimal shock waveform that would accomplish defibrillation with minimal delivered energy. It was shown that morphologically distinct waveforms have different defibrillation efficacies in both experimental studies (18,19,26,32,42) and theoretical studies using lumped models (16,43). However, the experimental studies that elucidate mechanisms for differences in defibrillation efficacies of the various waveforms are lacking.…”
mentioning
confidence: 99%
“…However, previous experimental studies have already demonstrated that a monophasic ascending ramp (AR) waveform has higher defibrillation efficacy compared with the descending ramp (DR) waveform, with the rectangular waveform having an intermediate efficacy (29,32,41). Furthermore, a study using the modified Blair model demonstrated that the monophasic AR waveform has better polarization efficacy than the monophasic exponential decaying waveform (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It follows from this model that trian gular ascending pulses and triangular descending pulses of the same pulse time should have the same threshold amplitude of defibrillation current and the same thresh old defibrillation energy. However, it was shown experi mentally that a triangular ascending pulse required lower defibrillation energy (lower current amplitude) compared to a triangular descending pulse [2,3].The characteristic energy method suggested in this work provides theoretical assessment of monopolar defib rillation pulse efficiency. This method allows pulses of dif ferent shape to be tested and optimal defibrillation pulse time to be determined for elucidation of this difference.…”
mentioning
confidence: 95%
“…A arquitetura do desfibrilador de descarga capacitiva de onda trapezoidal apresenta outra variante do desfibrilador por descarga capacitiva simples, na qual controlam-se os momentos inicial e final de descarga para evitar, por um lado, o elevado pico inicial de tensão, que geralmente ocasiona arritmias pós desfibrilatórias, além de danos ao miocárdio e, por outro lado, a suave e lentíssima descarga residual, denominada de "rabicho", que tende a refibrilar o coração [27].…”
Section: Monofásicaunclassified